Postępowanie w sprawie skargi na czynności egzekucyjne - Drelichowska, Angelika (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article presents the problems of proceedings in case of a complaint against enforcement actions in Polish administrative enforcement proceedings. The main goal of the paper is to analyse the specificity as well as the course of proceedings in such case. Analyzing and contrasting domestic regulations of both administrative proceedings and administrative enforcement proceedings, the author reaches the conclusion that the proceedings in case of a complaint against enforcement actions should be assessed as positive, although some provisions of the Act on Administrative Enforcement Proceedings require some changes. The author also discussed the legal consequences of the inadmissibility of a complaint against enforcement actions and inadmissibility of the legal actions in judicial administrative proceeding in cases of complaints against orders issued in the proceedings in case of a complaint against enforcement actions.
Keywords: administracyjne postępowanie egzekucyjne; zażalenie na czynności egzekucyjne; przebieg postępowania; czynności egzekucyjne; postanowienia wydane w administracyjnym postępowaniu egzekucyjnym